“I AM A WIDOW, POOR AND LIVING IN A VILLAGE”: WHAT’S CHANGED AFTER THE BEIJING DECLARATION IN RURAL INDONESIA? (Proceedings of the International Conference on Future of Women, 2025)
Widows in rural Indonesia, tethered by the invisible threads of tradition, navigate a landscape where patriarchal norms cast long shadows over their autonomy and rights. This article explores the experience of three widows living in three villages in rural West Java, Central Java, and Central Kalimantan. It examines how their lives have changed since the adoption of the Beijing Declaration 30 years ago. Using a narrative approach, the research zooms into the personal stories of these women to understand their experiences with social attitudes, their role within the community, and their strategies for dealing with economic deprivation. Observation and in-depth interviews were conducted to collect the data. The result portrays that although the Beijing Declaration has brought positive changes such as improved access to economic opportunity, and education for their family, significant challenges persist. By highlighting the resilience and agency of these women as they navigate and challenge the patriarchal structure, the study emphasizes the urgency of social support and legal reforms in strengthening their socio-economic status. Through the widows’s narrative, this paper tells both progress and persistent struggles, manifesting a nuanced perspective on the impact of international gender equality commitment at the grassroots level. These unique experiences of widows in rural Indonesia contribute to the broader discourse on pursuing gender equality in the rural context, as well as provide recommendations for marching the Beijing Declaration.
Keywords: widow; gender discrimination; Beijing declaration; rural Indonesia; economic empowerment; narrative inquiry